Internationalization of law : Globalization, international law and complexity - Varella, Marcelo Dias (Springer Berlin Heidelberg, 2014)
The book provides an overview of how international law is today constructed through diverse macro and microprocesses that expand its traditional subjects and sources, with the attribution of sovereign capacity and power to the international plane (moving the international toward the national). Simultaneously, national laws approximate laws of other nations (moving among nations or moving the national toward the international), and new sources of legal norms emerge, independent of states and international organisations. This expansion occurs in many subject areas, with specific structures: commercial, environmental, human rights, humanitarian, financial, criminal, and labor law contribute to the formation of postnational law with different modes of functioning, different actors, and different sources of law that should be understood as a new complexity of law.